Well‐Dispersed Nickel‐ and Zinc‐Tailored Electronic Structure of a Transition Metal Oxide for Highly Active Alkaline Hydrogen Evolution Reaction - Ling, Tao; Zhang, Tong; Ge, Binghui; Han, Lili; Zheng, Lirong; Lin, Feng; Xu, Zhengrui; Hu, Wen‐Bin; Du, Xi‐Wen; Davey, Kenneth; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2019)
The practical scale‐up of renewable energy technologies will require catalysts that are more efficient and durable than present ones. This is, however, a formidable challenge that will demand a new capability to tailor the electronic structure. Here, an original electronic structure tailoring of CoO by Ni and Zn dual doping is reported. This changes it from an inert material into one that is highly active for the hydrogen evolution reaction (HER). Based on combined density functional theory calculations and cutting‐edge characterizations, it is shown that dual Ni and Zn doping is responsible for a highly significant increase in HER activity of the host oxide. That is, the Ni dopants cluster around surface oxygen vacancy of the host oxide and provide an ideal electronic surface structure for hydrogen intermediate binding, while the Zn dopants distribute inside the host oxide and modulate the bulk electronic structure to boost electrical conduction. As a result, the dual‐doped Ni, Zn CoO nanorods achieve current densities of 10 and 20 mA cm−2 at overpotentials of, respectively, 53 and 79 mV. This outperforms reported state‐of‐the‐art metal oxide, metal oxide/metal, metal sulfide, and metal phosphide catalysts. A controlled tailoring of electronic structure of an oxide for the hydrogen evolution reaction (HER) is reported. Dual Ni and Zn doping is shown to be responsible for a significant increase in the HER activity of the host oxide, which was previously considered as catalytically inactive. The engineered oxide nanorods exhibit significantly high HER activity and are amongst the most active reported.